Prospective, observational study of carbon dioxide gaps and free energy change and their association with fluid therapy following cardiac surgery. Issue 2 (14th October 2019) - Mahendran, Sajeev; Nguyen, John; Butler, Ethan; Aneman, Anders
Abstract : Background: Venoarterial carbon dioxide pressure (pv‐a CO2 ) and content (Cv‐a CO2 ) differences, including the ratio to arteriovenous oxygen content difference (Ca‐v O2 ), and free energy changes (−∆∆Ga‐v ) may reflect tissue hypoperfusion. The associations with changes in cardiac output (CO) or oxygen consumption (VO2 ) following fluid bolus administration were investigated. Methods: Single‐centre, observational study of 89 adult post‐operative cardiac surgical patients admitted to ICU. The pv‐a CO2, Cv‐a CO2 and their ratios to Ca‐v O2 as well as the −∆∆Ga‐v were determined before and after a 250‐500 mL fluid bolus using arterial, central venous and mixed venous blood gas analyses. Responses associated with changes ≥ or <15% in CO or oxygen consumption (VO2 ) were compared. Results: In 234 boluses, the mixed venous to arterial pv‐a CO2 and its ratio to Ca‐v O2 were independently associated with an increase in CO; odds ratio 1.3 (95% CI 1.1‐1.5) and 1.7 (95% CI 1.5‐1.9) respectively, P  < .001) and VO2 ; odds ratio 2.1 (95% CI 1.3‐3.1), P  < .001 for Ca‐v O2 . No measures of pv‐a CO2, Cv‐a CO2 or related ratios to the Ca‐v O2 were associated with an increase in CO ≥15% following a single volume bolus. The mixed venous and central venous Cv‐a CO2 to Ca‐v O2 ratios were different for the first bolus episode only; mean differences 0.81 (95% CI 0.13‐1.5), P  = .02 and 0.44 (95% CI 0.06‐0.82), P  = .02, respectively, for increased VO2  ≥ 15%. The −∆∆Ga‐v did not change. Conclusion: The venoarterial carbon dioxide gradients and related calculations to assess the adequacy of tissue perfusion before a fluid bolus were not associated with subsequent increases in CO of oxygen consumption. Editorial Comment In some shock conditions, regional tissue hypoperfusion can be obvious and arterio‐venous differences for CO2 or O2 may reflect this. This is not always the case; sometimes there are A‐V differences or even a high lactate level without any obvious regional tissue hypoperfusion. Fluid therapy is a cornerstone in shock resuscitation treatment, but determining optimal fluid therapy is challenging, particularly as fluid overload may be detrimental. Fluid challenges are used as an "ex juvantebus" method to dose fluid therapy, but it is not clear if a positive response reflects a state of hypoperfusion or the existence of a cardiac reserve. Still, a better understanding on how to target and guide fluid therapy is welcome, and studies digging into the problem are needed. Here, invasively monitored post‐operative cardiac surgery patients are assessed as a model to investigate if carbon dioxide gaps and free energy charge may be useful in detecting possible tissue hypoperfusion.